KONTRIBUSI LIMBAH DOMESTIK PENDUDUK DI SEKITAR SUNGAI BIKNOI TERHADAP KUALITAS AIR BENDUNGAN BIKNOI SEBAGAI SUMBER BAKUAIR MINUM SERTA UPAYA PENANGANANNYA - Maya Roman; Fransiskus Kia Duan; Suwari Suwari (Bumi Lestari Journal of Environment, 2016)
Biknoi River is potential to be polluted by domestic cesspool because it crosses settlement area. It is important to be paid more attention because the water from Biknoi River is used as the basic source of Municipal Waterworks (PDAM) of Kupang town. The aims of the research are identifying the society along the riversides’ habitual in throwing out the domestic cesspool which potential to reduce the quality of the water in that river, evaluating the waters’ quality, knowing the contribution of the society’s domestic cesspool towards the water’s quality in Biknoi dam, knowing the level of water pollution by using Pollution Index method and knowing the effort for solving this problem.This research combined physical research and social research. Physical research was done by chemistry analysis for the sample of water, while the social research was done by having an interview which used questionnaire. The result of this research showed that there was a strong relationship between the society’s habitual with the reduce of the water’s quality of Biknoi River. The reduce of the water’s quality showed by the result of pollution enumeration index i.e. medium pollution category. The biggest pollution is COD i.e. 28.996 ton / month. The effort to solve this problem is by making the society to be aware, cesspool management, aware of rules, critical area rehabilitation, real action, controlling and layout.